Pelatihan Penyusunan Laporan Keuangan Berbasis Digital Pada UMKM di Kota Palangka Raya: Digital-Based Financial Report Preparation Training for Micro, Small, and Medium Enterprises in Palangka Raya City - Putra, Kharisma Nugraha; Alexandro, Rinto; Amelia, Verra Rizki; Widyaningsih, Dhina Sri; Mentari, Theresia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The progress and success factors of Micro, Small, and Medium Enterprises (MSMEs) lie in how they utilize accounting information when making business decisions to manage their operations. One form of such accounting information is the financial reports of Micro, Small, and Medium Enterprises (MSMEs). The purpose of conducting Community Engagement (PkM) in the form of training for digital-based financial report preparation and reporting for MSMEs in Palangka Raya City is to assist MSME entrepreneurs in composing and generating financial reports for their businesses using technological advancements. The community engagement took place at the Central Kalimantan Directorate General of Treasury Office. The training was held on Thursday, July 6, 2023, and was attended by 15 participants, comprising MSME entrepreneurs from Palangka Raya City. The participants were motivated to enhance their financial administration practices, ensuring that they can create well-structured financial reports for their businesses using digital accounting applications. These reports can then be used by the entrepreneurs themselves for making business decisions, as well as by external parties for providing funding or credit to MSME entrepreneurs in Palangka Raya City.